2020
DOI: 10.3390/chemengineering4030051
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Metals by Sulphide Precipitation Using Na2S and HS−-Solution

Abstract: Precipitation of metals as metal sulphides is a practical way to recover metals from mine water. Sulphide precipitation is useful since many metals are very sparingly soluble as sulphides. Precipitation is also pH dependent. This article investigates the precipitation of metals individually as sulphides and assesses which metals are precipitated as metal hydroxides by adjustment of the pH. The precipitation of different metals as sulphides was studied to determine the conditions under which the HS− solution fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Whilst sulphide precipitation according to equations ( 1) and ( 2) correlated with strong smell H2S releases, during experiment was only detected in M1 and M3 (Table 4). It confirmed that in M2 reactors IOP Publishing doi:10.1088/1755-1315/1201/1/012076 7 with pH reached 8.7, the sulphide precipitation was weak and hydroxide precipitation as the primary mechanism [21]. Ammonia was detected high all reactors water except water from M4 and M5.…”
Section: H2s Nh3n and Srbsupporting
confidence: 61%
“…Whilst sulphide precipitation according to equations ( 1) and ( 2) correlated with strong smell H2S releases, during experiment was only detected in M1 and M3 (Table 4). It confirmed that in M2 reactors IOP Publishing doi:10.1088/1755-1315/1201/1/012076 7 with pH reached 8.7, the sulphide precipitation was weak and hydroxide precipitation as the primary mechanism [21]. Ammonia was detected high all reactors water except water from M4 and M5.…”
Section: H2s Nh3n and Srbsupporting
confidence: 61%
“…The precipitation efficiency recorded for Cu, Zn and Ni sulfides was 99.9%, 99.4 % and 99.0%, respectively. An additional advantage of increasing the pH with NaOH before the sulfide precipitation was avoiding the generation of gaseous H 2 S, widely known as a flammable, corrosive and highly toxic compound [56].…”
Section: Discussionmentioning
confidence: 99%
“…This noticeably immobilizes the bio-available fraction of HMs and reduced their accumulation in the system [39][40][41]. On the other side, the application of Na 2 S performs this job in two mechanistic ways: first, by forming sodium hydroxide (NaOH) and hydrogen sulphide (H 2 S) in the system which immobilizes HMs as metal sulphide ensuing the reduction with H 2 S followed by precipitation with NaOH [42], and second, by producing hydroxides during the dissolution process which in turn form metal hydroxide and increases pH. This is in the line of work of Lewis [43] who detected such a mechanism while working with cadmium.…”
Section: Discussionmentioning
confidence: 99%